Pengembangan buku saku digital berbasis STEM terhadap kemampuan pemecahan masalah matematis siswa pada materi bilangan bulat kelas VII SMP Negeri 1 Embaloh Hulu - Hardianus Tomi; Dwi Oktaviana; Hartono hartono (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aims to develop a STEM-based digital pocket book to improve students’ mathematical problem-solving abilities on the topic of integers for seventh-grade students at SMP Negeri 1 Embaloh Hulu. This study employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through indirect communication techniques and measurement techniques, using expert validation sheets, practicality questionnaires, and posttest questions. The research sample consisted of 28 students from class VII A. The data analysis techniques included validity, practicality, and effectiveness analyses.The results showed that the developed STEM-based digital pocket book was categorized as very valid with a validity percentage of 90%, very practical with a practicality percentage of 91.5%, and effective with an effectiveness percentage of 67.86%. Therefore, the STEM-based digital pocket book is feasible for use in the mathematics learning process in schools. Keywords: Digital pocket book, problem-solving skills, STEM, integers